Hi all,
I want to calculate the expression by a recurrence equation but I got this error:
RSolve::litarg: To avoid possible ambiguity, the arguments of the dependent variable in Hypergeometric2F1[a,a,a+n,z] should literally match the independent variables. >>
the code is:
Code:
F[n_] := Hypergeometric2F1[a, a, a + n, z]
RSolve[{(n + a) (n + a - 1 - (2 n - 1) z) F[n] - (n + a) (n + a - 1) (1 - z) F[n - 1] + n^2 F[n + 1] == 0,
F[0] == ((a - 1) (1 - z))/(a - 1 + z) Hypergeometric2F1[a, a, a - 1, z]}, F[n],n]
Does anyone know where is wrong in my code or how to solve this problem?
Thanks in advance,
xdu